Beyond price tags and promotions: Investing in marketing values - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
Customers today look not only at the product, but also at value - not just economic value, but also, the social, environmental and ethical merits behind every purchase. For companies, particularly small to medium sized enterprises, simply hawking products will not cut it anymore, says marketing expert Gaurav Bhalla. Speaking at a Singapore Management University graduation ceremony, Bhalla shares his thoughts on the role of 'marketing' in attracting and retaining today's sophisticated consumers.